Smart Specialisation in the EU: Is it a Bridge between Innovation and Cohesion? - Argentino Pessoa (European Regional Science Association (ERSA), 2014)
Current innovation policy is the result of decades of research about the nature and role of innovation in economic growth. Such investigation has contributed to redesign our knowledge not only on the role played by innovation in economic development but also about the relationship between innovation and territory. Although the huge literature examining the relationships between territory and innovation has shown abundant evidence that certain regions are systematically more innovative than others the reasons for this dissimilarity go on being controversial. But, whatever the reason, the propensity for generation or absorption of innovation differs clearly between regions with some regions being characterised more by innovation-using rather than innovation-producing activities and others by a complete absence of innovation. Resulting from the criticisms to former policy approaches and from theoretical and empirical developments, the concept of ?smart specialisation' appeared and has gained significant political prominence in the European Union (European Commission, 2010; McCann and Ortega-Argilés, 2011). Although regions in many parts of the world are showing interest in the smart specialisation policy approach (OECD, 2012), it is Europe that takes the lead in this type of strategy, feeding high expectations about the results of this approach. In fact, European Commission sees smart specialisation as ?the basis for European Structural and Investment Fund interventions in research and innovation considered as part of the future Regional Policy's contribution to the Europe 2020 jobs and growth agenda'. Furthermore, the EC goes beyond the innovation policy domain and describes smart specialisation as involving ?a process of developing a vision, identifying competitive advantage, setting strategic priorities and making use of smart policies to maximise the knowledge-based development potential of any region, strong or weak, high-tech or low-tech'(S3 Platform website). This paper looks at the capacity of the smart specialization approach to attain the aims that it alleges to pursue, namely the aptitude to simultaneously respond to cohesion and innovation, questioning if smart specialization is able to bridge efficiency and equity which inspire innovation and cohesion, respectively.
Keywords: O31; O33; R11; R58; 330; Cohesion policy; European Union; Innovation; smart specialisation